(untitled) (Applied Biological Research, 2017)
The present study was conducted on Indian mynah, bulbul and sparrow with the aim to study their gross morphological features of sternum. Birds, three each of mynah, bulbul and sparrow, were collected dead and processed in air-tight jars, for 3 weeks. Morphometric measurements of sternum were carried out using standard methods. The study revealed that the anterior two-third of body in the sternum of mynah, unlike the posterior one-third, had a distinctly designed median groove. The sternal body in sparrow was divided into a concave anterior half and a flat posterior half. The lengths and width of sternum were highest in mynah. The length of sternum was nearly double the width in all three birds. The dorsal surface of sternum in bulbul, as compared to mynah and sparrow, was characteristically enriched by median pneumatic foramina. The rostrum was typically ‘Y’ shaped. The lateral border of sternum on either side displayed 5, 5 and 4 costal facets in mynah, bulbul and sparrow, respectively. The sternal keel was highly developed in all the 3 species of birds. The presence of highly developed keel is indication for strong flight capability of these birds. The study suggests that the presence of ՙY՚ shaped rostrum is a significant feature of passerine birds.